Excess sludge biochar facilitates persulfate activation for highly efficient tetracycline removal. (21st October 2022) - Lv, Bowen; Zhang, Weiliang; Liu, Yu; Xu, Dezhi; Fan, Xiulei
Abstract: This study proposed a novel advanced oxidation system to treat metal and antibiotic pollution in water simultaneously. Meanwhile, the enhancement effect of absorbed metal pollution on the activation of persulfate in the system was also investigated. As the most widely used and polluting material, tetracycline (TC) and metal Fe were used as the pollutant models. In this study, a carbonaceous material (BC) was prepared from excess sludge and then combined with the persulfate system (Fe/BC/PS). It was found that the best biochar was obtained when the pyrolysis temperature reached 500 °C (BC500), with the specific surface area of 39.712 m 2 /g. Combining it with 300 mg/L PS, the removal rate of 120 mg/L TC reached 70.6%. Moreover, the sludge biochar itself possessed numerous reaction sites and good defective structure, which provided a perfect reaction site for the variable metals absorbed by BC. They accelerated electron conduction greatly, which led to the activation of PS very active and generating far more active radicals than normal. In addition, it also proposed the rational pathway and potential mechanism of TC degradation based on the degradation intermediates. This study has a high reference value for resource utilization of sewage sludge and antibiotics removal from water. HIGHLIGHTS: The Fe/BC500/PS system significantly enhanced TC removal efficiency. Synergistic effect of adsorption and degradation showed stronger removal capacity. Electron transfer between Fe in various valence states is the main catalytic center. The generation of · OH and SO4 − is the leading mechanism for TC degradation. Perspective of in-situ utilization of residual Fe for BC application was discussed. Graphical Abstract